Voices in the Classroom: Intertextuality, Power, and Pedagogy in Indonesian EFL Discourse - Yelfiza Yelfiza; Della Patria; Ferlizea Marsya; Nofitri Nofitri (English Department FBS UNP, 2026)
This study explores how intertextuality constructs classroom discourse, shapes power relations, and guides pedagogy in Indonesian EFL (English as a Foreign Language) contexts. Using qualitative classroom discourse analysis, the research was conducted in three schools in Padang, Indonesia, involving three English teachers and their students. Data were collected from classroom video recordings, ethnographic notes, and teacher interviews. The analysis identified five intertextual themes: (1) moral legitimation through references to religion and national ideology; (2) epistemic framing via textbooks and curricula; (3) disciplinary socialization through teacher narratives and students’ experiences; (4) behavioral regulation through playful, game-like intertextuality; and (5) cognitive scaffolding through dialogic negotiation. These intertexts drew on vertical sources (Islamic texts, curricular norms, institutional rules) and horizontal sources (student utterances, peer talk, daily routines), producing a hybrid discourse of control, engagement, and moral guidance. The findings show that intertextuality functions beyond language, serving as a pedagogical resource for order, identity formation, and value transmission. In multilingual and multicultural classrooms, intertextual practices mediate teacher authority and student agency while embedding moral dimensions of learning. This study contributes to EFL discourse research by highlighting intertextuality as a critical tool for ethical and effective classroom communication.